Analysis of Students' Initial Ability Based on Generic Science Skills in Reaction Rate Material - Yani Kartini Situmorang; Marudut Sinaga; Ani Sutiani; Ratu Evina Dibyantini; Zainuddin Muchtar (Universitas Negeri Medan, 2023)
This writing aims to determine the validity of the test instrument and initial results scholastic ability test and KGS-based final evaluation test instrument on reaction rate material. This research uses Research and Development research and development methods. The research subject was class XI B which consisted of 36 students. This study used a scholastic test instrument and a final chemistry evaluation with 20 questions each. Based on the results of the validation test by the expert validator, it can be seen that the average percentage results obtained for Material Aspects are 87.08%, Construction Aspects are 87.92%, Language Aspects are 89.17%, and Additional Rules are 100%. The Scholastic test instrument consists of 20 questions that are tested on students namely; 17 valid questions and 3 invalid questions. The results of the final evaluation ability test were 20 items tested on students, 18 questions were valid and 2 questions were invalid. Scholastic ability test trials obtained namely; 3%